Concentration of 90Sr in grain on fuel traces of the Chornobyl radioactive fallout - L. N. Otreshko; S. E. Levchuk; L. V. Yoschenko (Âderna Fìzika ta Energetika, 2014)
During 2012 - 2014 sampling of soil and grain in Ivankiv district of Kyiv region at all fields adjacent to the ChNPP exclusion zone was carried out, where the cereal crops were planted. In all samples 137Сs and 90Sr activities were mea¬sured. Besides, in soil samples the exchangeable fractions of 90Sr and calcium and acidity of soil solution were determined. Dependence of 90Sr soil-grain transfer factors was specified. In conducting research works by sampling occurred 74.14-37-425:2006 SOU, SOU SOU 74.14-37-424:2006 and 01.1-37-426:2006. The activity of 90Sr was determined by standard radiochemical method.